2012
DOI: 10.4315/0362-028x.jfp-11-486
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Pepperoni Process for Control of Shiga Toxin–Producing Escherichia coli

Abstract: The objective of this study was to compare the survival of non-O157 Shiga toxin–producing Escherichia coli (STEC) with E. coli O157:H7 during pepperoni production. Pepperoni batter was inoculated with 7 log CFU/g of a seven-strain STEC mixture, including strains of serotypes O26, O45, O103, O111, O121, O145, and O157. Sausages were fermented to pH ≤4.8, heated at 53.3°C for 1 h, and dried for up to 20 days. STEC strains were enumerated at designated intervals on sorbitol MacConkey (SMAC) and Rainbow (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…While lower temperatures seem to protect vegetative pathogens such as E. coli O157:H7, Listeria, and Salmonella, ambient storage conditions in the range of 20 to 30uC increases bacterial lethality (26,36). The influence of temperature on pathogen survival under acidic conditions has also been reported for a variety of food products including orange and grapefruit concentrates (26), homemade mayonnaise and related products (29), homemade eggplant salad (35), and pepperoni (13).…”
Section: Resultsmentioning
confidence: 93%
“…While lower temperatures seem to protect vegetative pathogens such as E. coli O157:H7, Listeria, and Salmonella, ambient storage conditions in the range of 20 to 30uC increases bacterial lethality (26,36). The influence of temperature on pathogen survival under acidic conditions has also been reported for a variety of food products including orange and grapefruit concentrates (26), homemade mayonnaise and related products (29), homemade eggplant salad (35), and pepperoni (13).…”
Section: Resultsmentioning
confidence: 93%
“…In our study, no strain-dependent differences in the reduction kinetics of the EHEC strains tested were evident, indicating that the combination of increasing acidity and reduced a w and redox potential (E h ), together with the presence of preservatives, such as nitrite, and competitive microbiota, was effective at reducing the EHEC load in fermented sausages and, conversely, preventing EHEC growth. Glass et al, comparing the survival of non-O157 STEC strains (O26, O45, O103, O111, O121, and O145 serovars) with that of E. coli O157:H7 strains during pepperoni production, showed that O103 and O157 strains exhibited the highest survival rates (40). Consequently, processes suitable for controlling E. coli O157 would also be applicable to the inactivation of other STEC strains tested in the study (40).…”
Section: Discussionmentioning
confidence: 99%
“…Glass et al, comparing the survival of non-O157 STEC strains (O26, O45, O103, O111, O121, and O145 serovars) with that of E. coli O157:H7 strains during pepperoni production, showed that O103 and O157 strains exhibited the highest survival rates (40). Consequently, processes suitable for controlling E. coli O157 would also be applicable to the inactivation of other STEC strains tested in the study (40). Luchansky et al (41) investigated the thermal stability of E. coli O104:H4 and other STEC strains in ground beef and showed that the cooking times and temperatures effective for inactivating serotype O157:H7 in ground beef were equally effective against the seven non-O157:H7 Shiga toxin-producing strains, including the O104:H4 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Although not the sole/primary vehicle of sporadic cases and outbreaks, raw and further processed beef was responsible for several illnesses and recalls over the past 35 years (Griffin et al ., 2003 ; Kaspar et al , 2010 ; Page, 2018 ). Several reports have been published, particularly since the early- to mid-1990’s and likely in response to the much publicized salami outbreaks in the U.S. (CDC, 1995a) and Australia (CDC, 1995b), detailing the fate of serotype O157:H7 cells of STEC in a variety of both short- and longterm ripened cured-dried sausage and reporting on validated interventions and processes for their control (Balamurugan et al ., 2017 ; Calicioglu et al , 2002 ; Faith et al ., 1997 , 1998; Glass et al , 2012 ; Heir et al ., 2013 ; Holck et al ., 2011 ; Hinkens et al ., 1996 ; McLeod et al ., 2016 ; Riordan et al ., 1998 ; Rode et al ., 2012 ). As detailed in our previous publication (Hinkens et al ., 1996 ), although there are a variety of pepperoni types and sizes, three main categories dominate the market: i) small diameter (28-36 mm) for the deli case, ii) medium diameter (49-55 mm) for pizza topping, and iii) large diameter (60-80 mm) for sandwiches.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of a study by Glass et al . ( 2012 ) wherein strains of the six regulated non-O157:H7 serotypes of STEC were evaluated, most prior studies evaluated the fate of serotype O157:H7 strains of E. coli in dry-fermented-type sausage (Faith et al , 1997 , 1998; Hinkens et al ., 1996 ; Riordan et al ., 1998 ). Given the current regulatory posture that The Big Six strains of non-O157:H7 serotypes and strains of O157:H7 are considered adulterants in raw/non-intact meats (USDA-FSIS, 2011), further studies are warranted to validate the comparative fate of these additional STEC strains/serotypes of E. coli in fermented meats.…”
Section: Introductionmentioning
confidence: 99%